Methodology for Design of an Intelligent Transport System (ITS) Architecture for Intermediate Colombian City (2019)
(Eng) Colombia has a high death rate due to traffic accidents, compared to the world reference. In particular, intermediate cities of the country have a very high death rate due to traffic accidents, much higher than the national rate and large cities rate. Municipal - ities and mobility secretariats have tried to solve these problems through the development of technological services, within the framework of the so-called Intelligent Transportation Systems (ITS). However, in most cases, these services are not based on an adequate ITS architecture, therefore, interoperability and integration of services is not feasible, generates high costs and its implementation is complex to carry out. The development of the services is not based on ITS architecture, due to the fact that this architecture has not been developed. Although there are works related to regional ITS architectural design methodologies, there is no methodology that considers diverse sources of reference and the particular context of the city. To encourage the de- velopment of mobility services, using an appropriate ITS architecture, we develop a methodology to design it in an intermediate city of a developing country. To formulate the methodology, we review the related documentation; we identify best practices; we consider the scope and context; and finally, we defined a logical process that was easy to implement. The present article details design methodology that we elaborate and presents the results obtained when applying the methodology in a particular case. Methodology obtained allowed the design of an ITS architecture for city of Popayán , in addition we consider that it serves as a tool for development of ITS architectures in similar contexts. ITS architecture designed will allow to plan and implement the mobility services of the city in an appropriate way.